Factors that influence the quality of nursing care at Kafue district hospital - Hichilema, Nosiah Kabbudula (Lusaka: University of Zambia , School of Medicine, 2005)
The study sought to determine factors that influence the quality of nursing care at kafue district hospital. The respondents were selected from four wards within the hospital. The study was done during the months of August to September 2004.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Care of the sick; Nursing --Quality control; Nursing Care --standards --Zambia.